Visual documentation and biotopic distribution of opisthobranch species in the Akkum-Erdemli Region (Türkiye) - Ã‡ete, Ertuğrul; Ayas, Deniz; Ergüden, Deniz (Universitas Malikussaleh, 2025)
This study presents a preliminary assessment of opisthobranch sea slug diversity in the coastal waters of Erdemli-Akkum, located in Mersin Bay (Eastern Mediterranean, Türkiye). During exploratory scuba dives conducted between 2014 and 2015, seven species belonging to different opisthobranch groups were observed and photographed across a range of marine biotopes, including rocky substrates, sandy bottoms, and macroalgal assemblages. The recorded taxa include Goniobranchus annulatus, Flabellina rubrolineata, Flabellina affinis, Cratena peregrina, Elysia viridis, Aplysia depilans, and Syphonota geographica. These species represent a broad ecological and morphological diversity within the subclass Heterobranchia. The findings contribute to the growing faunistic inventory of opisthobranchs in the Eastern Mediterranean and highlight the ecological richness of the Akkum coastal area. The use of in situ photography proved valuable for documentation and visual identification, supporting future taxonomic and ecological studies. Keywords: Eastern Mediterranean; Mersin Bay; Nudibranchs; Opisthobranchia; Photographic records